ACQUISITION OF ARABIC AS A SECOND LANGUAGE IN EARLY CHILDREN IN ISLAMIC KINDERGARTEN - Aziz, Abdul; Niswah, Siti Khoirun; Ibrahim, Faisal Mahmuoud Adam (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
It is believed that memorizing the Qur’an would be able to improve the acquisition of a second language, especially Arabic language, particularly for early childhood. This is because children have quite sharp hearing, so they quickly acquire Arabic language as their second language. The language acquisition is done by listening and kinesthetic methods. For this purpose, the study aims to describe the process of acquiring Arabic in early childhood at Daarut Tahfidz lil Athfal Malang. Researchers applied descriptive qualitative research and case study methods. Data obtained by observation and interviews. The results showed that learning activities to memorize the Qur’an can accelerate language acquisition in early childhood who previously had not been able to pronounce sentences perfectly. At the opening and closing of the lesson, the teacher in the class always reminds the mufradât (vocabulary) that has been delivered, so that it will strengthen their memory in Arabic language. The research is expected to provide an overview of the importance of providing Arabic language learning from an early age in order to strengthen Islamic teachings from an early age.